A comparative molecular and 3-dimensional structural investigation into cross-continental and novel avian Trypanosoma spp. in Australia - Crystal Cooper; R. C. Andrew Thompson; Adriana Botero; Amanda Kristancic; Christopher Peacock; Yaowanuj Kirilak; Peta L. Clode (Parasites & Vectors, 2017)
Abstract Background Molecular and structural information on avian Trypanosoma spp. throughout Australia is limited despite their intrinsic value in understanding trypanosomatid evolution, diversity, and structural biology. In Western Australia tissue samples (n = 429) extracted from 93 birds in 25 bird species were screened using generic PCR primers to investigate the diversity of Trypanosoma spp. To investigate avian trypanosome structural biology the first 3-dimensional ultrastructural models of a Trypanosoma spp. (Trypanosoma sp. AAT) isolated from a bird (currawong, Strepera spp.) were generated using focussed ion beam milling combined with scanning electron microscopy (FIB-SEM). Results Here, we confirm four intercontinental species of avian trypanosomes in native Australian birds, and identify a new avian Trypanosoma. Trypanosome infection was identified in 18 birds from 13 different bird species (19%). A single new genotype was isolated and found to be closely related to T. culicavium (Trypanosoma sp. CC2016 B002). Other Trypanosoma spp. identified include T. avium, T. culicavium, T. thomasbancrofti, Trypanosoma sp. TL.AQ.22, Trypanosoma sp. AAT, and an uncharacterised Trypanosoma sp. (group C-III sensu Zidková et al. (Infect Genet Evol 12:102-112, 2012)), all previously identified in Australia or other continents. Serially-sectioning Trypanosoma sp. AAT epimastigotes using FIB-SEM revealed the disc-shaped kinetoplast pocket attached perpendicular to the branching mitochondrion. Additionally, the universal minicircle sequence within the kinetoplast DNA and the associated binding protein were determined in Trypanosoma sp. AAT. Conclusions These results indicate that bird trypanosomes are relatively conserved across continents, while being locally diverse, which supports the hypothesis that bird trypanosomes exist as fewer species than described in the literature. Evidence exists that avian Trypanosoma spp. are infecting mammals and could be transmitted by haemadipsid leeches. Trypanosoma sp. AAT is most likely a separate species currently found only in Australia and the first 3-dimentional ultrastructural analysis of an avian trypanosome provides interesting information on their morphology and organelle arrangement.